2022
DOI: 10.1002/smll.202107238
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Stable 1T‐MoS2 Doped with Ni Single Atoms for Water Splitting in Alkaline Media

Abstract: Metallic MoS2 (i.e., 1T‐MoS2) is considered as the most promising precious‐metal‐free electrocatalyst with outstanding hydrogen evolution reaction (HER) performance in acidic media comparable to Pt. However, sluggish kinematics of HER in alkaline media and its inability for the oxygen evolution reaction (OER), hamper its development as bifunctional catalysts. The instability of 1T‐MoS2 further impedes its applications for scaling up, calling an urgent need for simple synthesis to produce stable 1T‐MoS2. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 84 publications
5
68
0
Order By: Relevance
“…In one of their works, Wang et al introduced ascorbic acid (AA) in a simple one-step hydrothermal process, and found that flower-shaped 1T-MoS 2 could be collected at low temperatures and 2H-MoS 2 at high temperatures (>200 °C) (Figure 9C). [133] The XRD patterns of the product samples showed that the interlayer distance of MoS 2 was 9.65 Å and that of 2H was 6.3 Å. The synthesis mechanism of 1T phase was as follows: AA was dehydrogenated during the reaction to generate dehydrogenated ascorbic acid, which was inserted between MoS 2 layers and prompted and its XRD patterns.…”
Section: Direct Phase-controlling Synthesesmentioning
confidence: 96%
See 4 more Smart Citations
“…In one of their works, Wang et al introduced ascorbic acid (AA) in a simple one-step hydrothermal process, and found that flower-shaped 1T-MoS 2 could be collected at low temperatures and 2H-MoS 2 at high temperatures (>200 °C) (Figure 9C). [133] The XRD patterns of the product samples showed that the interlayer distance of MoS 2 was 9.65 Å and that of 2H was 6.3 Å. The synthesis mechanism of 1T phase was as follows: AA was dehydrogenated during the reaction to generate dehydrogenated ascorbic acid, which was inserted between MoS 2 layers and prompted and its XRD patterns.…”
Section: Direct Phase-controlling Synthesesmentioning
confidence: 96%
“…Ni-, Co-, Fe-doped flower-like 1T-MoS 2 were obtained by introducing transition metals. [133] The results showed that Ni1T-MoS 2 had enhanced catalytic activity for both HER and OER reactions in alkaline medium, and the atomic doping of Ni was proven to be the key for HER/OER performance improvement. In Gudal et al's study, a phosphorus-doped ultrathin 1T-copper molybdenum disulfide (P1T-CMS) multifunctional electrocatalyst for water separation was developed, and the catalyst showed good catalytic effect for both HER and OER.…”
Section: Dopingmentioning
confidence: 97%
See 3 more Smart Citations